Analysis of Factors Influencing Students' Decision-Making in Choosing Islamic Boarding School at Nahdlatul Wathan Islamic Centre - Syahrul Bahri; Wasiman Wasiman (Jurnal Pendidikan Indonesia, 2025)
This study employs a quantitative research approach to investigate the factors influencing decision-making at Pondok Pesantren Islamic Centre Nahdlatul Wathan. Quantitative research utilizes structured tools such as surveys to gather numerical data, focusing on quantifying relationships and behaviors and employing statistical techniques to test hypotheses. Conducted during the 2023/2024 academic year, the research involved 100 respondents selected through purposive sampling, comprising 22 vocational school students and community members surrounding the boarding school in Tanjung Riau, Batam. Data were collected using an online questionnaire with a 5-point Likert scale and analyzed using SPSS 21 for multiple linear regression to explore the impact of independent variables (Price, Location, Promotion) on the decision to choose the boarding school. Findings reveal that Price significantly affects decision-making (regression coefficient B = 0.299, t-value = 3.222), indicating that higher prices increase the likelihood of choosing the boarding school. Location also has a substantial impact (B = 0.657, t-value = 6.793), suggesting that a strategic location enhances the probability of selection. Promotion shows a significant effect (B = 0.306, t-value = 4.739), albeit slightly weaker than Location. Overall, the multiple linear regression analysis demonstrates the model's significance (F-value = 17.183), implying that Price, Location, and Promotion collectively influence the decision to choose a boarding school. These insights are crucial for educational institutions aiming to understand key decision-making factors.